React architecture : working with Flux and Redux (O'Reilly, 2017)
"In this course, you'll learn about the fundamentals of state management and how Flux and Redux fit as great tools for React. You'll learn the core concepts of Flux and Redux and gain some hands-on experience by applying them to a React notepad project. The course is designed for intermediate-level developers with JavaScript and ES6 experience plus some history in building React applications."--Resource description page